PERSEPSI DIRI GAYA BERPAKAIAN SECARA MUSLIMAH (STUDI DESKRIPTIF MAHASISWI FAKULTAS ILMU SOSIAL DAN ILMU POLITK UNIVERSITAS RIAU) - Gusriady, Ridwan Febrian; Yazid, Tantri Puspita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Allah obligates for Islamic women to wearing muslim clothing for cover his private partswho is not mahram. Muslim clothing weared for closing her genitals in various activities. InIndonesia, muslim clothing has become a fashion trend because of manyused by artists, thataffect adolescents included in Pekanbaru, especially in the Faculty of Social and PoliticalSciences, University of Riau. Basically nospecific regulations that require student using muslimclothing in a campus and that make various self perceptions. This study aims to determine thefactors that influence the self perception and to know the process formation of self-perceptionamong student of the Faculty of Social and Political Sciences,University of Riau.This research used qualitative method research. Informants in this study were 12 femalestudents of the Faculty of Social and Political Sciences, University of Riau that used muslimclothing and selected by using purposive sampling technique and accidental sampling. Data wascollected through observation, interviews, and documentation. Data analysis techniquesincluded at collection, data reduction, organizing data as well as the conclusion of the exposureand verification.These results indicate that the process of formation the perception created by the style ofdress of muslim student of the Faculty of Social and Political Sciences, University of Riauthrough clothing size close the genitals, made of thick and loose, dark color, body movementsthat keep it from the male, always use muslim clothing in any activity, feel more protected fromthe hot sun, understand how the criteria of muslim dress according to religious teachings ofIslam, as well as have a favorable view of muslim clothing. And than their perception is alsoinfluenced by several factors, including changing attitudes for the better, the feeling of beingcomfortable and calm, has a back ground based of islam education, has many friends in sociallife, saving when use the money, the past experiences that triggerto use muslim clothing,have abest friend who likes to use muslim clothing, and was active in Islamic organizations.Keywords: communication, persepticion, clothing muslim, fashion style